The quorum-sensing regulator ComA from Bacillus subtilis activates transcription using topologically distinct DNA motifs - Wolf, Diana (Nucleic Acids Res, 2016)
ComA-like transcription factors regulate the quorum response in numerous Gram-positive bacteria. ComA proteins belong to the tetrahelical helix-turn-helix superfamily of transcriptional activators, which bind as homodimers to inverted sequence repeats in the DNA. Here, we report that ComA from Bacillus subtilis recognizes a topologically distinct motif, in which the binding elements form a direct repeat. We provide in vitro and in vivo evidence that the canonical and non-canonical site play an important role in facilitating type I and type II promoter activation, respectively, by interacting with different subunits of RNA polymerase. We furthermore show that there is a variety of contexts in which the non-canonical site can occur and identify new direct target genes that are located within the integrative and conjugative element ICEBs1. We therefore suggest that ComA acts as a multifunctional transcriptional activator and provides a striking example for complexity in protein–DNA interactions that evolved in the context of quorum sensing.